2014
DOI: 10.1007/s00726-014-1880-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of the resistant and susceptible genotypes of maize infected with sugarcane mosaic virus

Abstract: Protein phosphorylation plays a pivotal role in the regulation of many cellular events. No information is yet available, however, on protein phosphorylation in plants in response to virus infection. In this study, we characterized phosphoproteomes of resistant and susceptible genotypes of maize (Zea mays L.) in response to Sugarcane mosaic virus (SCMV) infection. Based on isotope tags for relative and absolute quantification technology, TiO2 enrichment method and LC-MS/MS analysis, we identified 65 and 59 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…Ferritin gene expression is modulated by various environmental factors, including the intensity of drought, cold, light and pathogenic attack 41 . It has also been reported that the phosphorylation level of ferritin was significantly changed under virus infection in maize, which indicated that the phosphorylation of ferredoxin might play a positive roles in maize for the resistance to pathogen infection 33 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Ferritin gene expression is modulated by various environmental factors, including the intensity of drought, cold, light and pathogenic attack 41 . It has also been reported that the phosphorylation level of ferritin was significantly changed under virus infection in maize, which indicated that the phosphorylation of ferredoxin might play a positive roles in maize for the resistance to pathogen infection 33 .…”
Section: Resultsmentioning
confidence: 92%
“…The expression of SR protein under different environmental cues suggests they have an important role in plant defense and HR-like cell death 32 . It has been reported that the phosphorylation level of arginine SR splicing factor was significantly changed both under biotic and abiotic stresses 26 33 . In this study, the phosphorylation level of the arginine SR splicing factor was relatively stable from 1 to 4 h after SA treatment, but from 4 to 9 h, there was a sharp increase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the large subunit of RuBisCO accumulated in resistant maize inoculated with SCMV (Wu et al 2013a;Wu et al 2015). Chloroplast localized ferredoxin V and thioredoxins was also upregulated (Cao et al 2012;Cheng et al 2008;Wu et al 2015). Taken together with interactions of SCMV viral proteins with the RuBisCo small subunit and ferredoxin (Cheng et al 2008;Leng et al 2017), the results suggest an intimate relationship between photosynthetic activity and potyvirus infection.…”
Section: Genomic and Transcriptomicmentioning
confidence: 84%
“…Increased expression of transcripts for genes important for photosynthesis has been noted in some systems. For example, the large subunit of RuBisCO accumulated in resistant maize inoculated with SCMV (Wu et al 2013a;Wu et al 2015). Chloroplast localized ferredoxin V and thioredoxins was also upregulated (Cao et al 2012;Cheng et al 2008;Wu et al 2015).…”
Section: Genomic and Transcriptomicmentioning
confidence: 99%